2016
DOI: 10.1039/c5nj01099c
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of photochemical heterogeneous water oxidation by a manganese based soft oxometalate immobilized on a graphene oxide matrix

Abstract: Enhancement of photochemical water oxidation using a graphene oxide matrix for [Na17[Mn6P3W24O94(H2O)2]·43H2O@GO] soft-oxometalate is shown.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 70 publications
0
13
0
Order By: Relevance
“…46 The catalytic activity of SOMs has also been explored in various types of reactions viz., in photo-polymerization [54][55][56] and photochemical water oxidation. 57 In this article we have shown that SOM type materials based on oxo-molybdate and oxo-tungstate clusters can efficiently catalyse the reduction of CO 2 to HCOOH/HCHO by transferring the electrons and protons generated from oxidation of water. The catalysts reported here present a new opportunity as they provide a method that is scalable and fast with a very high turnover number.…”
Section: Introductionmentioning
confidence: 99%
“…46 The catalytic activity of SOMs has also been explored in various types of reactions viz., in photo-polymerization [54][55][56] and photochemical water oxidation. 57 In this article we have shown that SOM type materials based on oxo-molybdate and oxo-tungstate clusters can efficiently catalyse the reduction of CO 2 to HCOOH/HCHO by transferring the electrons and protons generated from oxidation of water. The catalysts reported here present a new opportunity as they provide a method that is scalable and fast with a very high turnover number.…”
Section: Introductionmentioning
confidence: 99%
“…Also polyoxometalates are photoactive and generally stable under photochemical conditions. POMs have been used as photocatalyst in different photopolymerization reaction and organic reactions by us already [38][39][40][41][42]. Thus we are now interested to use those giant POMs in photo catalytic organic coupling reaction.…”
Section: Introductionmentioning
confidence: 99%
“…POMs are generally ionic in nature with high charge and a number of hydrogen bonding sites, which provides the possibility to synthesize composites with different electro active surfaces such as graphene, graphene oxide, different LDHs ,. The immobilization of the POM moiety on the electro active surface can enhance the catalytic activity of these materials ,. POMs can also exist in a colloidal state of soft‐oxometalates (SOMs) .…”
Section: Introductionmentioning
confidence: 99%
“…POMs can also exist in a colloidal state of soft‐oxometalates (SOMs) . We have recently shown that soft oxometalates based on several different oxometalates can act as active catalyst for photo chemical oxidation of water without the need of a photosensitizer and a sacrificial electron donor , Further CO 2 can be transformed into other energy dense organic compounds like formic acid and formaldehyde by H 2 O in presence of light using SOMs .…”
Section: Introductionmentioning
confidence: 99%